Simulasi Pengembangan Bengkel Fabrikasi Jurusan Pendidikan Teknik Mesin Sesuai Kaidah 5S Menggunakan Aplikasi 3ds Max - Hargiyarto, Putut; Ismara, Ketut Ima; Suyanto, Suyanto; M. Khairudin, M. Khairudin (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of this study were to assess the risks involved in workshops, to apply the Seiso, Seiton, Seiri, Seiketsu, Shitsuke (5S) concept for workshops development and to develop the fabrication workshop for the Department of Mechanical Engineering Education, Faculty of Engineering, YSU using the 3DS Max simulation application. This study was categorised into Research and Development. The first steps were designing and creating the product using 3DS Max application. The next step was testing the product by implementing it to perform the workshops policy. The results of this study showed the risks consisted of noise, strong light, harmful gases and the mechanical hazards due to falling and moving objects. The implementation of 5S concept, K3 and ergonomics were required to maintain the regularity, efficiency and work discipline, to prevent and to minimize workplace accidents. The development of fabrication workshops using the 3DS Max simulation applicationis is beneficial for implementing the aspects of 5S, K3, ergonomics and provides a reference in redesigning a workshop.